1992
DOI: 10.1073/pnas.89.7.3145
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary restriction on immune function and development of autoimmune disease in BXSB mice.

Abstract: Chronic energy intake restriction (CEIR) prolonged the median life span and inhibited autoimmunity and development of autoimmune disease in BXSB mice, as has been established for mice of several other autoimmune-prone, short-lived strains. Whether imposed just after weaning or delayed until manifestations of disease had appeared, CEIR inhibited or reversed development of autoimmunity and immune complex-based renal disease in male BXSB mice. CEIR also prevented the formation of anti-DNA antibodies and preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
1
18
0
1
Order By: Relevance
“…The effect of fasting was assessed in a randomized, single-blind controlled trial (Kjeldsen-Kragh et al, 1991). This beneficial effect on autoimmune disease is also consistent with the results of an animal study (Kubo et al, 1992). However, to demonstrate an evidence of clinical use, there are still few data about the DR and human inflammatory disease.…”
Section: Dietary Restriction (Dr) For Future Clinical Usementioning
confidence: 57%
See 2 more Smart Citations
“…The effect of fasting was assessed in a randomized, single-blind controlled trial (Kjeldsen-Kragh et al, 1991). This beneficial effect on autoimmune disease is also consistent with the results of an animal study (Kubo et al, 1992). However, to demonstrate an evidence of clinical use, there are still few data about the DR and human inflammatory disease.…”
Section: Dietary Restriction (Dr) For Future Clinical Usementioning
confidence: 57%
“…Animal studies have shown that DR can prevent or lessen the severity of cancer (Chen et al, 1990), stroke (Yu and Mattson, 1999), coronary heart disease (Ahmet et al, 2005), autoimmune disease (Kubo et al, 1992), allergy (Nakamura et al, 2004), and Parkinson's disease and Alzheimer's disease (Mattson et al, 2003). Thus, evidence is now strong for the association between DR and disease protection in experimental animals.…”
Section: Dietary Restriction (Dr) For Future Clinical Usementioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that CR can exert positive effects upon the life span and certain age-related diseases (2,8,14,39,40,43,53,54,71,76,79). This study demonstrated that a period of CR can attenuate sickness behavior following LPS administration.…”
Section: Perspectives and Significancementioning
confidence: 59%
“…The fact that our results are in close agreement suggests that dietary restriction did not confound our findings. Indeed, numerous reports indicate that mild dietary restriction can prolong life span, ameliorate age-related declines in physiologic functions, and reduce the incidence of autoimmune disease (Weindruch and Walford, 1988;Kubo et al, 1992). The fact that these results were highly replicable also highlights the utility of iontophoretic cell loading, which facilitates more precise morphometry relative to the Golgi technique by ensuring that cells are completely filled and by eliminating overlapping dendritic fields.…”
Section: Discussionmentioning
confidence: 71%